2018
DOI: 10.3390/ijms19082434
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Nerve Differentiation of Mesenchymal Stem Cells Derived from Long-Term Cryopreserved Human Dental Pulp In Vitro and Analysis of Their Motor Nerve Regeneration Potential In Vivo

Abstract: The reduction of choline acetyltransferase, caused by the loss of cholinergic neurons, leads to the absence of acetylcholine (Ach), which is related to motor nerve degeneration. The aims of the present study were to evaluate the in vitro cholinergic nerve differentiation potential of mesenchymal stem cells from cryopreserved human dental pulp (hDPSCs-cryo) and to analyze the scale of in vivo motor nerve regeneration. The hDPSCs-cryo were isolated and cultured from cryopreserved dental pulp tissues, and thereaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Our study indicates that pulp-derived MSCs had higher proliferation rate than papilla, and follicle-derived MSCs. The phenotyping of three types of MSCs demonstrated the MSC-like phenotypic features and our results are in accordance with the previous results [18,25,33,34]. MSCs from dental pulp, papilla, and follicle tissues expressed key pluripotent transcription factors such as OCT4, SOX2, and NANOG invariably both at mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study indicates that pulp-derived MSCs had higher proliferation rate than papilla, and follicle-derived MSCs. The phenotyping of three types of MSCs demonstrated the MSC-like phenotypic features and our results are in accordance with the previous results [18,25,33,34]. MSCs from dental pulp, papilla, and follicle tissues expressed key pluripotent transcription factors such as OCT4, SOX2, and NANOG invariably both at mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 92%
“…MSCs were isolated from human dental pulp, papilla, and follicle tissues of a single tooth donor sample as previously described [25]. In brief, third molar were collected from male donors aged 14-18 years at the Department of Oral and Maxillofacial Surgery at Changwon Gyeongsang National University Hospital following approval by the Institutional Review Board of the University Hospital, and with the informed consent of enrolled patients for their tissue donation (GNUH IRB-2012-09-004).…”
Section: Isolation Of Mscs From Dental Tissue and In Vitro Culturementioning
confidence: 99%
“…When cultured in neuronal inductive conditions for an extended period of time, DPSCs exhibit a neuronal morphology and express neuronal-specific markers such as PSA-NCAM, β -III tubulin, neurofilament-M, and nestin, showing the ability to generate a sodium current consistent with functional neuronal cells [ 70 ]. Moreover, DPSCs transplanted in vitro can generate functional neurons and improve nerve regeneration [ 71 , 72 ]. In addition, several studies also showed that DPSCs exhibit the capacity to acquire the phenotype of endothelial cells and generate vascular-like structures [ 73 76 ].…”
Section: Dpscsmentioning
confidence: 99%
“…Since then, MSCs have been proven to be derived from virtually all tissues' adventitial progenitor cells and pericytes [15]. The most applied tissues include the bone marrow [16], cord cells [17], adipose tissue [18], molar cells [19], amniotic fluid [20], and placenta [21], as well as several solid organs, such as the lung [22], liver [23], and kidney [24]. These MSCs from solid organs are referred to as tissue-resident MSCs [25].…”
Section: Introductionmentioning
confidence: 99%